Overlay Fiber Network Based MNRs for P2P Networks - A. Polar; M. Bunruangses; K. Luangxaysanam; S. Mitatha; P.P. Yupapin (My University, 2012)
This paper propose a new design for a P2P overlay network over fiber optic communication that uses dense wavelength division multiplexing (E-DWDM) wavelength enhancement that can be used to generate the new optical communication bandwidths (wavelength bands) using a Gaussian pulse propagating within a MNRs, whereas the virtual P2P overlay networks are increased in channel capacity and signal security which can be provided. The increasing in number of channel can be obtained by increasing in the wavelength density, while the security is introduced by the specific wavelength filter, which is operated by the optical network and directly link with other nodes. The theoretical wavelength enhancement generation is reviewed. The advantage is that the proposed system can be implemented and used overlapping with the existed fiber optic communication link, where the privacy can be provided, which is discussed in details.
Keywords: Overlay network; Optical Network Technologies